2022
DOI: 10.1021/acsami.2c05085
|View full text |Cite
|
Sign up to set email alerts
|

Nonplanar Spray-Coated Perovskite Solar Cells

Abstract: Spray coating is an industrially mature technique used to deposit thin films that combines high throughput with the ability to coat nonplanar surfaces. Here, we explore the use of ultrasonic spray coating to fabricate perovskite solar cells (PSCs) over rigid, nonplanar surfaces without problems caused by solution dewetting and subsequent "run-off". Encouragingly, we find that PSCs can be spray-coated using our processes onto glass substrates held at angles of inclination up to 45°away from the horizontal, with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Although we have used spin-coating to deposit the solution-processable device layers (np-SnO 2 electrontransport layer, TC perovskite precursor, and spiro-OMeTAD hole-transport layer), we note that such layers can be deposited via spray-coating, allowing devices to be created over complex, curved substrates. [29] Our devices are fabricated directly onto a surface that could have a significant second function-e.g., acting as the wing of an aircraft or the roof of a car. To estimate the specific power of our devices, we simply consider the masses of the layers that we have deposited.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although we have used spin-coating to deposit the solution-processable device layers (np-SnO 2 electrontransport layer, TC perovskite precursor, and spiro-OMeTAD hole-transport layer), we note that such layers can be deposited via spray-coating, allowing devices to be created over complex, curved substrates. [29] Our devices are fabricated directly onto a surface that could have a significant second function-e.g., acting as the wing of an aircraft or the roof of a car. To estimate the specific power of our devices, we simply consider the masses of the layers that we have deposited.…”
Section: Discussionmentioning
confidence: 99%
“…Critically, the ability to process PSCs from solution using techniques such as spray coating allows them to be deposited over curved surfaces. [ 29 ] PSC devices on CFRP composites could be readily employed in unmanned aerial vehicles (UAVs) and high‐altitude pseudo‐satellites (HAPSs), where there are stringent weight limitations and finite fixed wingspans. [ 30 ] Indeed, it has been demonstrated that by integrating solar cells over curved surfaces, devices can be realized having a power output exceeding that of planar cells occupying an equivalent area.…”
Section: Introductionmentioning
confidence: 99%
“…Solution processing methods for organic and perovskite thin films, such as scraping, [33,34] spraying, [35–37] spin‐coating, [38] roll‐to‐roll printing [39,40] and inkjet printing, [41] have the advantages of simple process, low cost and the ability to achieve large‐area processing. The processing methods are suitable for automated HT film preparation.…”
Section: Automation Laboratory Equipmentmentioning
confidence: 99%
“…Organic semiconductor devices can also be deposited via droplet-based techniques such as spray coating. Spray coating offers several key advantages over competing deposition processesthe most significant of which being that its noncontact nature permits materials and devices to be fabricated over nonplanar surfaces . Furthermore, spray coating has been estimated to have a far lower initial investment cost than techniques such as blade coating .…”
Section: Introductionmentioning
confidence: 99%